Implementation IoT On Electrical Monitoring And Consumption Recording System With Web Server And Spreadsheet Integration - Catur Pamungkas; Jarot Dian Susatyono; Nur Rokhman (Jurnal Transformatika, 2026)
Uncontrolled electrical energy consumption can cause energy waste and increase operational costs, especially in industrial environments with multiple electrical distribution panels. Conventional power meters that only display data locally without historical data storage make monitoring and evaluation processes less effective, making it difficult to analyse electricity usage and identify potential energy waste. This study purpose to make an IoT b electrical energy monitoring system using ESP32, PZEM-004T sensor, and automatic relay control. The system can do monitoring several parameters like voltage, current, power, and energy consumption in real time through a Wi-Fi network. In addition, electricity usage data are automatically stored to google spreadsheet for analysis and energy efficiency evaluation. The proposed system is aim the effectiveness and efficiency of electricity monitoring, simplify energy management, and help reduce energy waste and operational costs through more optimal electrical energy utilization.